College physics with an integrated approach to forces and kinematics - Giambattista, Alan (McGraw-Hill, 2020)
College Physics, Fifth Edition, presents a unique "forces first" approach to physics that builds a conceptual framework as motivation for the physical principles. That intuitive approach, combined with a consistent problem-solving strategies, stunning art, extensive end-of-chapter material, and superior digital support make Giambattista a product that addresses the needs of TODAY's students. The 5th edition adds more applications to real-life, more problems, and highlights support for math skills needed for physics.